Integrative morphological, cytogenetic and molecular characterization of the Andean climbing catfish Astroblepus mindoensis (Regan, 1916) (Siluriformes:Astroblepidae) - Nirchio, Mauro; Oliveira, Claudio [UNESP]; de Bello Cioffi, Marcelo; Sassi, Francisco M. C.; Rizzi, Francisco Provenzano; Benavides, Santiago Wladimir Núñez; Berrones, Alison Jazmín Calderón; Romero, Juan Francisco Rivadeneira; Deon, Geize Aparecida; Kuranaka, Mariana [UNESP]; Valdiviezo-Rivera, Jonathan Santiago; Carrión Olmedo, Julio C.; et al. (Wiley, 2025)
Astroblepus species, commonly known as Andean climbing catfish, exhibit a unique challenge in species delimitation, leading to ongoing taxonomic debates. Here we report data on Astroblepus mindoensis, a vulnerable species endemic to Ecuador, obtained by an integrative approach that includes cytogenetic analysis, molecular identification of the specimens, and recording of morphological and morphometric characters useful for species diagnosis. Thus, this study aimed to associate the karyotype data of the specimens analyzed with morphological and molecular characters, improving and expanding the existing taxonomic information, thus contributing to the systematics of the species. Our morphology results, unlike Regan's original description, which is brief and ambiguous, provide a more detailed morphometric and meristic description. Molecular phylogenetic reconstruction and genetic distance based on a fragment of the cytochrome c oxidase subunit I (COI) showed that our samples constitute a well-supported and monophyletic clade within the A. grixalvii species complex. The cytogenetic analysis identified distinct chromosomal markers, including a single cluster of major ribosomal genes (on chromosome pair 3) and of minor ribosomal genes (on chromosome pair 12) with their localization differing from those reported in other Astroblepus species analyzed. Additionally, the presence of a heteromorphic chromosome pair in males suggests the presence of an XX/XY sex-determination system that has not been identified in other congeneric species. Further investigation is necessary to determine if these chromosomes are associated with the accumulation of repeated sequences, as typically occurs with sex chromosomes, and to assess their presence in other species of the genus.
Keywords: DNA barcoding; FISH; phylogeny; sex chromosomes; species delimitation